STRATEGI PEMASARAN PRODUK SKIN CARE TRUSTEE - ESIKA WAHASRI (Media Bisnis, 2015)
The short-term strategy is market penetration. The first step implementing a market penetration strategy is to determine the framework Segmenting, Targeting and positioning for determining the target market and positioning. Profile target market is young people who are active, dynamic, tend to be loyal, residing in urban areas, are very easily influenced in making purchasing decisions, like quality products and like to spend time on the internet in addition to watching TV. Promotion by making promotional program through the Above The Line and Below The Line in today's market by using everyday language both terms or phrases popular. Strategy Above The Line is done by loading ads in magazines, radio and internet. Below The Line can be done by providing free consultation on Ristra House, program sales promotion and trade promotion.